Refining the Occurrence of Viral Encephalopathy and Retinopathy, Photobacteriosis, and Vibriosis in Connection with Seawater Physicochemical Parameters: A Five-Year Case Study - SPINOS, EFTHIMIOS; KATSELIS, GEORGE; VALSAMIDIS, MICHAIL AGGELOS; WHITE, MARI DANIELLA; BAKOPOULOS, VASILEIOS (Mediterranean Marine Science, 2024)
The marine environment and its physicochemical parameters play a pivotal role in the context of fish farming. Fundamental physicochemical factors of water, including temperature (T°C), salinity (S psu), dissolved oxygen (D.O. mg/l), and pH, exert a profound influence on the physiology of farmed aquatic animals and the composition of microbial communities. This study aimed to establish correlations between documented disease occurrences in sea bass intensive rearing and the prevailing physicochemical parameters of water. The objective was to analyse the significance of these parameters in disease outbreaks and develop a predictive model for the outbreak risk of key diseases. To this end, real-time physicochemical data were collected daily over five years (2011-2015) from two fish farms (A and B) located in the Gulf of Argostoli, island of Cephalonia, Western Greece. The focus was on incidences of Viral Encephalopathy and Retinopathy (VER), Photobacteriosis caused by Photobacterium damselae subsp. piscicida (PHDP) and Vibriosis caused by Vibrio anguillarum serotype O1 (VAO1). Statistically significant correlations were found between increasing water temperature and salinity and the occurrence of VER, PHDP, and VAO1 diseases. The reduction of dissolved oxygen, when combined with other parameters, synergistically triggered the manifestation of these three diseases. The study’s findings were discussed within the context of their potential to predict disease outbreaks based on fluctuations in the physicochemical parameters of water and anticipated climate change scenarios.